1975
DOI: 10.1055/s-0028-1097771
|View full text |Cite
|
Sign up to set email alerts
|

PHARMACOCHEMICAL INVESTIGATION OF THE RAW MATERIALS FROM PASSIFLORA GENUS – 2. The pharmacochemical estimation of juices from the fruits ofPassiflora edulisandPassiflora edulisformaflavicarpa

Abstract: The contents and the composition of the alcaloids and flavonoids complex in the juices of the Passiflora edulis SIMS fruits, in the yellow and red fruit form, are evaluated. Furthermore the content of vitamin C and of the carotenoide dyestuffs was determined. The presence o f tanning agents so.as anthocyans was not 06served. O n the base of the pharmacodynamic investigation it was found, that the juice besides the ntrtritive propertiesacts tranquilizing, due to the presence of small quantities of alcaloids fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Unlike previous studies of β-carboline alkaloids from passionfruit, which were based on conventional phytochemical studies, 1,8 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous studies of β-carboline alkaloids from passionfruit, which were based on conventional phytochemical studies, 1,8 …”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding their economic relevance, the literature lacks investigations into the alkaloids from P. alata and P. edulis fruits by LC-MS techniques. Lutomski et al 8 identified alkaloids from P. edulis f. flavicarpa juices only by thin layer chromatography (TLC) combined with detection using Dragendorff's reagent.…”
Section: Introductionmentioning
confidence: 99%
“…1) and probably maltol (Hegnauer, 1990). It is still not clear which group of constituents is responsible for the pharmacological activities and both the flavonoids and the harman alkaloids have been considered to be the active principles (Ambuhl, 1966;Poethke et al, 1970;Lutomski et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…1 Passionfruit also contains about 14.45 g of sugar/100 g of edible portion, including fructose, glucose, and sucrose, along with seven others in trace amounts. 2,3 Ascorbic acid is present at 45 mg/8-oz serving, although levels may depend upon how the juice was processed and stored.…”
Section: Introductionmentioning
confidence: 99%